CHANGES IN SOIL NITROGEN AVAILABILITY IN RESPONSE TO A PRESCRIBED FIRE IN A MEDITERRANEAN FOREST (Pinus halepensis) ECOSYSTEM AROUND MONTPELLIER CITY, SOUTH OF FRANCE. - Rachid, A. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Ecosystem fire can variably affect soil nitrogen availability, which is a determinant factor for soil fertility and environmental issues. This research was conducted to study changes in soil nitrogen forms in Aleppo pine (Pinus halepensis) forest ecosystem, located in the south of France bordering Montpellier city, subjected to a prescribed fire of low intensity on 30 March 2011. Soil ammonium (NH4+-N), nitrates (NO3–N), and total nitrogen contents were measured, for two depths (0-2 and 2-10 cm), immediately before and after burning for five consecutive months. In parallel, produced nitrogen dynamics (net mineralization, immobilization, and losses by leaching and root absorption) was investigated using field incubation of identical soil samples in situ for three sequences of six weeks. As an immediate response of burning, NO3–N content at 0-2 cm depth reduced significantly (P = 0.05) by 62%, but NH4+-N content increased significantly (P = 0.01) by 14 times. Thus, transforming organic nitrogen in mineral nitrogen, mineralization, which is here focused on ammonium amount, raised considerably by almost 3 times. These results suggest that a low intensity fires programmed and executed during a cool season, may limit the total ecosystem nitrogen losses reported by several researches. Throughout the study, the burned sites had greater rates of nitrification, meaning that nitrogen was being processed more quickly through the ecosystem than that without a prescribe fire. Differently from nitrates, ammonium is subjected to intense immobilization and seasonal variations. At 2-10 cm depth, no significant effects on nitrogen forms were detected, with the exception of high NO3–N concentration. This case raises the question of the effect of burning on the movement of nitrates in the depth of the soil and its potential impacts on groundwater pollution.